2007
DOI: 10.1002/jbm.b.30999
|View full text |Cite
|
Sign up to set email alerts
|

Y‐TZP zirconia run against highly crosslinked UHMWPE tibial inserts: Knee simulator wear and phase‐transformation studies

Abstract: Our laboratory knee wear simulation appeared very supportive of the 9-year YZr/PE clinical results with Bi-Surface total knee replacements in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
2
8
0
1
Order By: Relevance
“…With a spatial resolution of 1 m, it was possible to map the transformation rate of used zone, and to compare them with surface roughness measurement [13,14].…”
Section: Quantitative Measurement Of Monoclinic Zirconia Volumementioning
confidence: 99%
“…With a spatial resolution of 1 m, it was possible to map the transformation rate of used zone, and to compare them with surface roughness measurement [13,14].…”
Section: Quantitative Measurement Of Monoclinic Zirconia Volumementioning
confidence: 99%
“…Currently, Yttria-stabilized tetragonal zirconia polycrystal (hereon: zirconia) is the most studied ceramic, mainly due to its high modulus of elasticity (White et al, 2005), wear resistance (Tsukamoto et al, 2008), strength and most importantly, its toughness (Guazzato et al, 2004a). These properties enabled zirconia to be milled through CAD/CAM procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The specific knee used in the previous study (Figure 1) used a bi‐surface design with a spherical cam that engages at 80° of flexion, however, because the flexion was 20° this cam had no influence on the wear 11, 46. Although the PE wear rates were less than those for a total hip under similar conditions, this is common due to the differences in kinematics and wear mechanisms between total hips and total knees 9, 10, 12, 22, 31.…”
Section: Discussionmentioning
confidence: 99%
“…A recent knee study showed that both increased crosslinking (35–70 kGy) and use of zirconia femoral condyles (Figure 1) reduced wear more than 60% 11. It was also noted that the Y‐TZP zirconia condyles did not exhibit phase transformation or other surface changes over five million cycle duration test 46. However, very little is known about how PE debris production will be affected by use of crosslinked PE and ceramic material combinations in knee joints.…”
Section: Introductionmentioning
confidence: 99%